간헐외사시에서 외직근 후전 후의 속발내사시 - 나경익; Kyeong Ik Na; 이주연; Joo Yeon Lee (Daihan angwa haghoi jabji, 2012)
목적: 간헐외사시 수술 후 속발내사시의 임상 경과에 대해 알아보고자 하였다. 대상과 방법: 기본형 간헐외사시로 외직근후전을 시행한 196명의 환자에서 속발내사시의 발생빈도, 위험인자, 사시각 변화, 치료결과 등을 분석하였다. 결과: 25명(12.8%)에서 속발내사시가 발생하였다. 속발내사시군에서 비속발내사시군에 비해 회선수직근 수술을 같이 시행한 경우가 더 많았고(p=0.001) 술후 1일의 과교정이 더 컸다(p=0.002). 술후 1일째 17PD 이상의 과교정 빈도는 비속발내사시군과 차이가 없었다. 25명 중 6명에서 재수술이 필요하였는데 이들 6명과 재수술 없이 회복된 환자들 간에 술후 1일의 과교정은 차이가 없었고, 전자는 내사시각이 증가하는 양상을 보여 술후 29.5개월에 최대 내사시각을 보였고 후자는 점차 감소하는 양상으로 술 후 4.3개월에 최대 내사시각을 보였다. 두 경우 모두 최종적으로는 내사시가 소실되고 좋은 입체시를 보였다. 결론: 속발내사시에서 외사시 수술 직후 과교정이 더 컸지만 이를 통해 속발내사시의 경과 및 예후를 예측하기는 어려운 것으로 나타났다. 간헐외사시 수술 후 발생한 속발내사시는 치료 후 양안시 기능이 보전되고 예후가 좋았다. Purpose: To evaluate the progress and outcome of consecutive esotropia after surgery for intermittent exotropia. Methods: The authors investigated the risk factors, changes in the angle of esodeviation and treatment outcome in consecutive esotropia after lateral rectus muscle recession for intermittent exotropia in 196 patients. Results: Consecutive esotropia occurred in 25 patients (12.8%). The patients underwent more frequent combined muscle surgeries on vertical and oblique muscles (p = 0.001) and had a greater amount of immediate postoperative overcorrection than subjects without consecutive esotropia. There was no significant difference with the incidence of overcorrection greater than 17 PD between the 2 groups with and without consecutive esotropia. There was no difference with the immediate postoperative overcorrection between the 6 cases that required surgery for their consecutive esotropia and the cases that recovered from their consecutive esotropia with conservative treatment. The former showed increasing esodeviation and maximum angle at average postoperative month 29.5. In the latter, esodeviation tended to decrease and showed maximum angle at average postoperative month 4.3. Finally, esotropia disappeared and good stereoacuity was obtained in both cases. Conclusions: Although subjects with consecutive esotropia had a greater immediate postoperative overcorrection than subjects without consecutive esotropia, the progress and outcome of consecutive esotropia following the initial overcorrection were not predictable. Consecutive esotropia after surgery for intermittent exotropia showed good overall outcome and well preserved stereoacuity after treatment.